Planning low carbon oriented retrofit of diesel-driven cranes to electric-driven cranes in container yards. (November 2022) - Lin, Shumin; Zhen, Lu; Wang, Wencheng
Abstract: Diesel-driven rubber-tired gantry cranes play an important role in the carbon emission and operating efficiency of the port. Retrofitting diesel-driven rubber-tired gantry cranes to electric-driven rail-mounted gantry cranes is one of the effective ways to reduce carbon emissions. However, the retrofit of diesel-driven rubber-tired gantry cranes will seriously affect the port's operating cost and operating efficiency. Therefore, this study investigates the retrofit problem of diesel-driven rubber-tired gantry cranes considering carbon emissions tax. The problem is described as a mixed-integer programming model that aims to minimize the sum of delay penalty cost, carbon emissions cost, and port investment cost. Two heuristic algorithms are designed to solve the model. Some acceleration strategies are proposed to improve the efficiency of the designed algorithms. Taking Jakarta International Container Terminal as a case study, a large number of numerical experiments are carried out to verify the efficiency of the designed algorithms. The results of the sensitivity analysis experiment show that the implementation of a carbon tax policy can promote the retrofit of rubber-tired gantry cranes, thereby reducing the carbon emissions of the port. Highlights: A retrofit plan model of RTGs is designed. Carbon emission tax policy and port investment decisions are considered. Acceleration strategies are applied to the designed heuristic algorithms. The impact of the retrofit of RTGs on the port's carbon emissions is analyzed.